Occlusal-masticatory function and learning and memory: Immunohistochemical, biochemical, behavioral and electrophysiological studies in rats - Toshihiro Hirai; Youngnam Kang; Hisashi Koshino; Katsuya Kawanishi; Yoshifumi Toyoshita; Yasuhiro Ikeda; Mitsuru Saito (Elsevier, 2010)
This review paper discusses the relationship between the mastication and learning and memory in rats. Immunohistochemistry of choline acetyltransferase (ChAT) showed that the numbers of ChAT-positive neurons in the nucleus of the diagonal band/medial septal nucleus (NDB/MS) of a powder diet group (PDG) and a molar crown-less powder diet group (MCPDG) were smaller than those of solid diet group (SDG). Subsequently, the concentrations of acetylcholine (ACh) in the hippocampus and in the cerebral cortex in MCPDG were significantly lower than that of SDG. The response latency of the MCPDG group was significantly shorter in passive avoidance tests. The impact of mastication on recovery of learning and memory function rats receiving permanent middle cerebral artery occlusion (MCAO) was also evaluated. In a Morris water maze task, rats fed a solid diet after MCAO surgery had greater functional recovery than rats fed a liquid. Finally, a whole-cell patch-clamp study revealed crucial roles of nitric oxide (NO) in the physiological control of cholinergic neurons in NDB/MS and in the pathogenic mechanism for cell death. Collectively, these results suggest key roles for NO both in the learning and memory function, and potentially in dementia. Mastication may have a significant impact on the maintenance and recovery of learning and memory, presumably through pathogenic and physiological mechanisms of NO action.